2019
DOI: 10.1002/jcb.29177
|View full text |Cite
|
Sign up to set email alerts
|

SKP2, positively regulated by circ_ODC1/miR‐422a axis, promotes the proliferation of retinoblastoma

Abstract: Retinoblastoma (RB) is the most common intraocular malignancy in infants and children. S‐phase kinase‐associated protein 2 (SKP2) has been unmasked as an oncogene in a great many of carcinomas. The biologic function and the detailed molecular mechanism of SKP2 in RB need to be better understood. In this study, real‐time quantitative polymerase chain reaction and Western blot showed the ectopic expression of SKP2 in RB tissues and cell lines. Loss of function assays showed the attenuated cell proliferation in R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 33 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…Functionally, circRNA participates in the formation of tumors, regulating malignant biological behaviors of cancer cells such as proliferation, apoptosis and metastasis. It is reported that circ_0001649 suppresses RB cell proliferation and apoptosis by inhibiting AKT/mTOR signaling pathway, and its low expression level indicates poor prognosis in patients [23]; circ_ODC1 positively regulates SKP2 and promotes RB cell proliferation [24]. In this study, we found for the first time that the expression level of circ_0000527 in RB tissues and cells was significantly increased, and its high expression was significantly correlated with the lower the degree of differentiation and increased cTNM staging.…”
Section: Discussionmentioning
confidence: 52%
“…Functionally, circRNA participates in the formation of tumors, regulating malignant biological behaviors of cancer cells such as proliferation, apoptosis and metastasis. It is reported that circ_0001649 suppresses RB cell proliferation and apoptosis by inhibiting AKT/mTOR signaling pathway, and its low expression level indicates poor prognosis in patients [23]; circ_ODC1 positively regulates SKP2 and promotes RB cell proliferation [24]. In this study, we found for the first time that the expression level of circ_0000527 in RB tissues and cells was significantly increased, and its high expression was significantly correlated with the lower the degree of differentiation and increased cTNM staging.…”
Section: Discussionmentioning
confidence: 52%
“…By means of qRT-PCR, we verified the negative correlation between the three miRNAs and three ubiquitination-related genes (CBL, SMURF2, and USP4), which are key components of the ubiquitin–proteasome system and have been shown to engage in the ubiquitination and degradation of some pivotal genes implicated in HTS [ 23 , 24 ]. Consistent with these findings, miR-422a was reported to directly target SKP2 [ 25 ], which is an E3 ubiquitin ligase and was confirmed to promote fibroblast proliferation in pulmonary fibrosis through via ubiquitin–proteasome pathway [ 26 ]. In addition, miR-2116-3p was shown to interact with and inhibit PIWIL1 [ 27 ], and silencing of PIWIL1 was reported to upregulate FBXW7 [ 28 ], which is a component of E3 ubiquitin-protein ligase complex and was observed to induce expression of fibrotic genes including fibronectin during pulmonary fibrosis [ 29 ].…”
Section: Discussionmentioning
confidence: 70%
“…For example, dysregulation of Skp2 expression plays a carcinogenic role in hematological malignancies [ 23 ]. The overexpression of Skp2 in retinoblastoma can restore suppressed retinoblastoma growth [ 24 ]. Therefore, many experts and scholars are using Skp2 as a target for cancer treatment to explore more cancer treatment methods.…”
Section: Discussionmentioning
confidence: 99%